(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
currently, the increase of nutrients, the increase of complex organic substances, the chemical composition of household appliances seriously affects the microbiology of the oral cavity and causes the increase of dental caries. Currently, its prevention is more important than the treatment of dental caries. This article provides information about dental caries disease, symptoms and treatment methods.